Pengelolaan Pajak Reklame: Upaya Meningkatkan Pendapatan Asli Daerah - Hudi, Moh. (As-Siyasi: Journal of Constitutional Law, 2022)
Tax is an important thing to be used as a means of carrying out government affairs, one of which is the advertisement tax. Based on Article 285 paragraph (1) letter a of Law Number 23 of 2014 concerning Regional Government, it is determined that the source of regional income consists of: regional original income which includes regional taxes. This study uses a qualitative descriptive method to get an overview and understanding of its relation to local tax revenue and management. The purpose of increasing regional tax revenues also includes increasing regional original income, so that regional taxes must always be increased to be used as much as possible in the interests of the people in accordance with the ideals of the nation, namely for the welfare of the people, the intellectual life of the nation and social justice. Advertisement taxpayers who are still not aware of their obligations to pay taxes and must also comply with applicable laws and regulations. Advertising must comply with applicable regulations cannot be installed in accordance with the wishes of the installation without heeding the applicable legal rules.